2003
DOI: 10.1002/ccd.10670
|View full text |Cite
|
Sign up to set email alerts
|

Nonionic low‐osmolar contrast media have no impact on major adverse cardiac events in patients undergoing coronary stenting with appropriate antiplatelet therapy

Abstract: The aim of this study was to assess the impact of two nonionic low-osmolar monomers (iopamidol and iopromide) and one ionic low-osmolar dimeric contrast medium (ioxaglate) on 30-day major adverse cardiac events in patients undergoing coronary interventions involving the use of new-generation stents and appropriate antiplatelet agents. Thirteen hundred and eight patients treated with stent implantation were randomized to receive ioxaglate (438 patients), iopamidol (442 patients), or iopromide (428 patients). Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This remains difficult to achieve in routine practice as the mean (SD) contrast dose in a randomised study with 1308 elective patients (with CKD present in only 2% of them) was 279 (106) ml 22. This study did not find any significant differences between non-ionic and ionic contrast agents.…”
Section: Contrast Agentsmentioning
confidence: 59%
“…This remains difficult to achieve in routine practice as the mean (SD) contrast dose in a randomised study with 1308 elective patients (with CKD present in only 2% of them) was 279 (106) ml 22. This study did not find any significant differences between non-ionic and ionic contrast agents.…”
Section: Contrast Agentsmentioning
confidence: 59%
“…There is some evidence to suggest that high‐osmolar CM are more likely to induce thrombosis than low‐osmolar or iso‐osmolar CM [32]. The differential effects between ICM and NICM on homeostasis have been the subject of controversies based on diverging study results, some studies suggesting that NICM are clearly more thrombogenic than ICM [4, 7–9, 11, 12, 17, 18, 21, 33] or at best neutral [5, 10, 13–16, 19], only one being in favor of NICM [6], most of them comparing the consequences of these effects on MACE following PCI (Table I). However, when combining data from studies which met criteria to be included in a metanalysis, Klein et al reported a substantial heterogeneity and an “overall” absolute difference in event rates of 4.6% in favor of ioxaglate which was nonsignificant given the wide confidence interval [20].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence showing that ionic low osmolar (ICM) (600–1000 mOsm/L) inhibits to a greater extent the coagulation cascade than nonionic iso‐osmolar (NICM) (280 mOsm/L) [1, 2] and does not activate resting platelets [3]. However, unlike experimental findings, the results of clinical trials comparing the effect of ICM and NICM to prevent percutaneous coronary intervention (PCI) complications remain divergent [4–19]. Several trials demonstrated better [4, 7–9, 11, 12, 17, 18] or neutral [5, 10, 13–16, 19] results with ICM and a single one was in favor of NICM [6] (Table I).…”
Section: Introductionmentioning
confidence: 99%
“…Scheller et al [96] reported that patients undergoing stent placement had fewer acute and subacute stent occlusions when imaged with ioxaglate (versus multiple non-ionic agents). However, Danzi et al [95] recently reported that non-ionic monomers (iopamidol and iopromide) did not adversely affect stent patency when compared with ioxaglate. The considerable peri-procedural use of antiplatelet agents may explain their results.…”
Section: Clinical Trialsmentioning
confidence: 95%
“…Randomized trials comparing ioxaglate with non-ionic monomers during PTCA have produced conflicting results [89][90][91][92][93][94][95]. In the two studies with the largest number of patients, one showed no significant difference between ioxaglate and iomeprol in the incidence of sudden vessel occlusion [93] while the other showed a trend towards fewer thromboembolic complications with ioxaglate compared with ioversol [94].…”
Section: Clinical Trialsmentioning
confidence: 99%